Will you eat your dog’s cookie? an exploration of relationship between consumer attitude and purchase intention in healthy food - Alexandra, Graciella; Mayangsari, Lidia (Journal of Innovation, Business and Entrepreneurship, 2019)
The food market is developing with a health benefit. However, health food tends to attract even more interest from consumer and businesses. Besides seeing the sense of meaning, food quality, and health of these foods, prices also greatly affect consumer attention. Snuupil Petcare is a company that runs in the pet care industry especially for dog products. This research is about how can we grow with a wider market, from only dog market and into human market. This research is to understand the relationship of consumer attitude and price perception in healthy dog cookies to the purchase intention decision. propose a growing business for Snuupil Petcare from dog market to a wider consumer market. Using the Multiple linear regression and descriptive analysis with online survey and product testing, the result customer attitude are have a really big role to the purchase intention, when human wants make a decision it affect by their attitude. Based on the analysis result after doing all the analysis, researcher will wider the Snuupil Pet Care especially for Snuupil cookies into human market, because there are really positive influence from the customer attitude to the healthy cookies even though it a dog cookies, and there are not really significant the price of the healthy cookies to the willingness to buy.Keywords: customer attitude, price perception, purchase intention, healthy food, price